General anthropometric and specific physical fitness profile of high-level junior water polo players - Kondric, M.; Uljevic, O.; Gabrilo, G.; Kontic, D.; Sekulic, D. (Journal of Human Kinetics, 2012)
The aim of this study was to investigate the status and playing position differences in anthropometric measures and specific physical fitness in high-level junior water polo players.